2015
DOI: 10.1177/1077559515580392
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Overrepresentation of Indigenous Children in Child Welfare Data

Abstract: Child welfare data collected for administrative purposes are often used as a source of information for understanding the population impact of child abuse and neglect (CA/N). This study used administrative data linked at the individual level for a cohort of Aotearoa New Zealand (NZ) children to follow and extend a model developed by Drake et al. In this investigation, we aimed to build an understanding of the high representation of indigenous NZ children in administratively sourced measures of CA/N. Variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 19 publications
0
50
0
Order By: Relevance
“…Underlying these factors are social structures affecting people's social position and life chances, including social class and race and incorporating a historical legacy as Cram et al (2015) argue. Demand interacts with the supply of servicesboth child welfare services and other formal and informal resources which may result in referrals or reports of children at risk -to produce intervention rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Underlying these factors are social structures affecting people's social position and life chances, including social class and race and incorporating a historical legacy as Cram et al (2015) argue. Demand interacts with the supply of servicesboth child welfare services and other formal and informal resources which may result in referrals or reports of children at risk -to produce intervention rates.…”
Section: Discussionmentioning
confidence: 99%
“…The categories, White, Black and Asian are very broad and encompass groups with very different histories and current circumstances (Cram et al, 2015). But, leaving those major problems on one side, why might the inverse relationship be evident for White but not for Black and Asian families?…”
Section: Explaining the Difference Between White And Ethnic Minority mentioning
confidence: 99%
See 1 more Smart Citation
“…In many countries, Indigenous and some ethnic groups are disproportionally represented in child welfare systems, representing inequalities in the chances of system contact (Cram, Gulliver, Ota, & Wilson, ; Fluke, Chabot, Fallon, MacLaurin, & Blackstock, ). Disproportionality can be defined as “… the state of being out of proportion … a condition that exists when the proportion of people of a certain race or ethnicity in a target population differs from the proportion of people of the same group in a reference population” (Detlaff, , p. 44).…”
Section: Inequalities Disproportionality and The Risk‐bias Debatementioning
confidence: 99%
“…Moreover, this review and the feasibility study identified the risk that predictive modelling would overpredict Māori child maltreatment and result in hypersurveillance of Māori whānau (Blank, et al, 2014;Wilson et al, 2015;Wilson & Cram, in press). A subsequent collaborative investigation of the potential for hypersurveillance did not resolve these issues, and urged caution in using and interpreting administrative data (Cram, Gulliver, Ota, & Wilson, 2015).…”
Section: Reflections On Linked Administrative Datamentioning
confidence: 99%